Evaluasi Implementasi Program Ekstakurikuler Pencak Silat di SMPN 220 Jakarta Barat - Novita Gratia (Peneliti.net, 2021)
This study aims to determine the context of implementing pencak silat extracurricular activities at SMPN 220 West Jakarta. readiness of human resources and supporting infrastructure for the program, the process of program implementation, and knowing the achievement of program implementation. The method used in this evaluation is descriptive qualitative method by looking at empirical data and facts. Data collection was carried out scientifically which included observation, structured interviews, and documentation. Interviews were conducted with school principals, deputy student principal, trainers, and students. Then the data is analyzed again using the source triangulation method, technical triangulation, and reduction analysis, data display, and congclusion. The conclusion of the evaluation research, that the background for the implementation of extracurricular pencak silat. There is a conformity between the vision and mission of the school and the vision of the mission of the martial arts mission, the absence of systematic socialization that is carried out in stages or formally, the absence of facilities or facilities provided by the relevant agencies so that the trainer takes a share from the program for program implementation, the mismatch of the process of implementing activities Pencak silat extracurricular activities and the response of parents to the implementation of pencak silat extracurricular activities are very positive and also the response of the parents of students is very supportive of the implementation of pencak silat extracurricular activities at the school. The implication of implementing this pencak silat extracurricular activity is that it can have an impact on students 'health, so that it gets a good response from the parents' team.